Biomechanical causes of trapeziometacarpal arthroplasty failure. Issue 11 (18th August 2017) - Spartacus, V.; Mayoly, A.; Gay, A.; Le Corroller, T.; Némoz-Gaillard, M.; Roffino, S.; Chabrand, P.
Abstract: Trapeziometacarpal joint prosthesis revision has been widely reported, mainly due to loosening of the trapezium cup. Our hypothesis is that current prostheses do not sufficiently respect the kinematics of this joint. CT scan acquisitions enabled us to determine the position of the first metacarpal relative to the trapezium in three different characteristic postures, in subjects in different stages of arthrosis. A CAD model of a current prosthesis was inserted into the numerical 3D model of the joint under the different postures. In the numerical model, we observe penetration of the cup by the head of the prosthesis. This virtual penetration could, in vivo, amount to overstressing the prosthetic elements, which would lead to loosening of the cup or of the metacarpal stem and luxation of the prosthesis.